Ultrasonic and electromagnetic NDE for structure and material characterization : engineering and biomedical applications - Kundu, T. (CRC Press, 2012)
"This textbook presents the latest advances in nondestructive evaluation (NDE) and features the incorporation of electromagnetic NDE techniques, which are the second most popular NDE method after ultrasonic NDE. With questions, problems, and worked out examples, the text describes biomedical applications and presents examples of modern NDE methods in the testing of medical devices. Contributors address such topics as cylindrical waveguide applications in ultrasonic evaluation, laser-ultrasonic techniques, structural health monitoring, acoustic microscopy, THz radiation, and fiber optics"--